Artificial texturing for enhanced soft elastohydrodynamic lubrication in total knee arthroplasty - Nirav Kantilal Meghpara; Punit Kumar; Gian Bhushan (International Journal of Thermofluids)
This study proposes the utilization of artificially textured surfaces to enhance film thickness in line contacts operating under soft elastohydrodynamic lubrication. Moreover, this investigation seeks to examine the effect of roughness of the surface, applied load, and average rolling speed on the efficacy of artificially textured surfaces in artificial knee joints, with the objective of enhancing the life of Total Knee Arthroplasty. The numerical analysis involves solving the elasticity and Reynolds equations. One of the two surfaces is artificially textured by superimposing a sinusoidal profile on its macro-geometry. The Newton-Raphson technique is employed to obtain the numerical solution of the governing equations discretized using the finite difference approach. For comparative analysis, both artificially textured and smooth surface conditions are individually considered in this study. The artificially textured surface exhibits a considerable enhancement in the thickness of the lubricating film compared to the smooth surface case under identical operating conditions. Furthermore, it is noted that the efficacy of the artificially textured surface becomes more evident at higher magnitudes of applied load and lower average rolling speeds. The significant enhancement up to 8 % in minimum film thickness achieved in this study represents a notable and valuable contribution to the field, underscoring its novelty and potential impact.